A ‘Child’s Vector’ in Guy Delisle’s Comics - Abriszewska, Paulina (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
The aim of the article is to study the influence of the child characters in Guy Delisle’s graphic stories on the narrative itself. This influence varies from direct and explicit (comments, characters’ actions) to indirect and implicit, when the very form of the narrative is reshaped. Such changes occur when the child character influences the way his or her father, who is allegedly the main character of the story, functions in relation to time and space. The article also focuses on how the child characters in the stories catalyze play with conventions or reflection about the self and about the medium. Sometimes these characters become protagonists whose perspectives dominate the narrative.